A Comparative E?cacy of MDCT Angiography and Colour Doppler Ultrasonography in Diagnosing Peripheral Arterial Disease in the Lower Limb - M B Naveen Raj; A. R Omprakash (Asian Journal of Medical Radiological Research, 2020)
Background: Imaging plays a crucial role in the management of patients with peripheral arterial disease. The present study compared colour Doppler ultrasonography findings with MDCT angiography in patients with peripheral arterial disease in the lower extremity. Subjects and Methods : 40 patients with signs and symptoms of peripheral arterial occlusive disease referred for evaluation by imaging by colour doppler ultrasonography and MDCT angiography were studied. Results: There was statistically significant difference in the detection of the extent of segment involvement in DFA. There is significant difference in the detection of the extent of segment involvement in popliteal artery. There is statistically extremely significant difference in the detection of the extent of segment involvement in ATA. Conclusion: MDCT is better than Doppler in detecting the length of stenosis in the arterial system. MDCT is better than Doppler in detecting the presence of thrombosis especially in the infra-popliteal segment. Even though MDCT is not statistically significant than Doppler in detecting the number of collateral segments , as the arterial tree is better delineated in MDCT.